Evaluation of Yantiin Kalabara – 5 Ways to a Healthier You: A primary school-based education program targeting healthy living choices through interactive workshops - Babic, Mark; Maynard, John; McLeod, Ruth; Ford, Claudine; Torell, Carla; Eather, Narelle (The Australian Journal of Indigenous Education, 2023)
The aim of this study was to develop, implement and evaluate the novel one-day, school-based health education program Yantiin Kalabara that embedded Aboriginal and Torres Strait Islander culture and perspectives within a series of interactive learning stations. In consultation with local Aboriginal and Torres Strait Islander community members, the program was designed to encourage healthy lifestyle choices and promote strong, sustainable and mutually respectful relationships between Aboriginal and Torres Strait Islander peoples and non-Aboriginal Australians. It involved five primary schools within the Awabakal, Wonnarua, Darkinjung and Worimi Countries (Australia) in movement-based and culturally rich learning activities. The feasibility of the program for use in primary schools and preliminary efficacy for affecting change in key health behaviours (physical activity, nutrition, screen-time) was assessed using student questionnaires. Yantiin Kalabara was delivered by the Hunter Primary Care team and volunteers. Students reported that it helped them improve their overall health, physical activity, eating habits and screen-time patterns. We have demonstrated that the program can be feasibly delivered in primary schools, and that the program was efficacious in affecting positive changes in key health behaviours of participating children. However, further evaluation in larger and more diverse populations using a randomised controlled trial is warranted.